(Radio)Biological Optimization of External-Beam Radiotherapy. (6th November 2012) - Nahum, Alan E.; Uzan, Julien
Abstract : "Biological optimization" (BIOP) means planning treatments using (radio)biological criteria and models, that is, tumour control probability and normal-tissue complication probability. Four different levels of BIOP are identified: Level I is "isotoxic" individualization of prescription dose D presc at fixed fraction number. D presc is varied to keep the NTCP of the organ at risk constant. Significant improvements in local control are expected for non-small-cell lung tumours. Level II involves the determination of an individualized isotoxic combination of D presc and fractionation scheme. This approach is appropriate for "parallel" OARs (lung, parotids). Examples are given using our BioSuite software. Hypofractionated SABR for early-stage NSCLC is effectively Level-II BIOP. Level-III BIOP uses radiobiological functions as part of the inverse planning of IMRT, for example, maximizing TCP whilst not exceeding a given NTCP . This results in non-uniform target doses. The NTCP model parameters (reflecting tissue "architecture") drive the optimizer to emphasize different regions of the DVH, for example, penalising high doses for quasi-serial OARs such as rectum. Level-IV BIOP adds functional imaging information, for example, hypoxia or clonogen location, to Level III; examples are given of our prostate "dose painting" protocol, BioProp . The limitations of and uncertainties inherent in the radiobiological models are emphasized.